Strategi Guru dalam Mewujudkan Active Learning Siswa di MTS Darul Amin Palangka Raya - Syamsudin, Dimas; Malisi, M. Ali Sibram; Muzakki , Muzakki (Jurnal Pendidikan Indonesia, 2025)
This study aims to describe teachers' strategies in implementing active learning for students in grade VIII, particularly in the subject of akidah akhlak at MTs Darul Amin Palangka Raya. The background of this study regarding the urgency of learning activities in the subject of akidah akhlak stems from students' lack of interest in learning. The learning method used are too monotonous, and students have difficulty understanding and remembering the material presented. This research employs a qualitative approach that emphasizes understanding phenomena in a natural and contextual manner. The data used in this study are primary and secondary data. Primary data was obtained directly from the sources being studied, including Akidah Akhlak teachers, the school principal, the vice principal in charge of the curriculum, and eighth-grade students. Secondary data consists of additional information such as classroom teaching documentation, student attendance records, textbooks, and other supporting materials. Data collection techniques included observation, interviews, and documentation. Based on the research results, akidah akhlak teachers use cooperative learning strategies with the Think Pair Share type, which involves forming study groups, solving problems through discussion, and then explaining and sharing the information obtained with the entire class. Students' interest in learning akidah akhlak is relatively good and more active, as evidenced by student attendance in each lesson, interview results, and field observation results.